The antiquity of the Sahara Desert: New evidence from the mineralogy and geochemistry of Pliocene paleosols on the Canary Islands, Spain - Muhs, Daniel R.; Meco Cabrera, Joaquín Francisco; Budahn, James R.; Skipp, Gary L.; Betancort, Juan F.; Lomoschitz, Alejandro (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
The Sahara is the largest warm desert in the world, but its age has been controversial, with estimates ranging from Miocene to Holocene. Mineralogical and geochemical data show that paleosols of Pliocene to mid Pleistocene age on Fuerteventura and Gran Canaria in the Canary Islands have developed in part from inputs of dust from Africa. These paleosols contain quartz and mica, minerals that are abundant in African dust but are rare in the basaltic rocks that dominate the Canary Islands. Trace elements with minimal mobility, Sc, Cr, Hf, Th, and Ta as well as the rare earth elements, show that paleosols have compositions that are intermediate between those of local rocks and African-derived dust. Thus, results reported here and in a recently published study by others indicate that 9 paleosols record delivery of African dust to the Canary Islands between similar to 4.8-2.8 Ma, similar to 3.0-2.9 Ma, similar to 2.3-1.46 Ma, and similar to 0.4 Ma. A long-term paleosol record of African dust input agrees with deepsea records off the coast of western Africa that imply increased dust fluxes to the eastern Atlantic Ocean at similar to 4.6 Ma. It is concluded that the Sahara Desert has been in existence as an arid-region dust source, at least intermittently, for much of the Pliocene and continuing into the Pleistocene.